Mina's story : a doctor's memoir of the holocaust - Deutsch, Mina 1911-2004 (ECW Press, 1994)
Mina Kimmel grew up in a small town in Galicia, eastern Poland, around the time of World War I. Because her hometown had no secondary school, she left home at 13 to pursue her education, and finally realized her dream of studying medicine in Czechoslovakia. There she met her future husband, Leon Deutsch, a fellow medical student, and spent some of the happiest years of her life. When the Nazi regime came to power, Mina and her husband lived each day in the shadow of the Holocaust. The young couple returned to Poland and fled further and further eastward with their infant daughter. They were put in charge of fighting a typhus epidemic in 17 villages under the Nazi occupation, and were later forced to hide in an underground bunker beneath a chicken coop until they were liberated by the Russians. The story ends in Canada, where Mina and Leon again had to struggle to establish themselves in their new country.